1996
DOI: 10.1159/000159187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiotensin II and Prostaglandins in Arcade Formation in a Developing Microvascular Network

Abstract: There are basically two types of branching patterns in the terminal part of the arteriolar tree. On the one hand, in a number of tissues, including the developing chick embryo chorioallantoic membrane (CAM), the pattern is dichotomous, whereas in other tissues many arteriolar-arteriolar connections, arcades, are found. The structure of the branching pattern depends on the local physical and chemical environment. The goal of this study was to investigate whether substances with an effect on vascular growth infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…This is controversial because quinapril, an ACE inhibitor, increased rather than decreased vascular density in a model of acute limb ischemia in the rabbit. 27 The proangiogenic activity of Ang II was first demonstrated on the chicken CAM by Le Noble et al 28 and later in a sponge model by Machado et al 29 This angiogenic effect of the renin system on microvessels has been documented in a model of electrical stimulation-induced angiogenesis. 30 It may seem paradoxical that the same molecule, AGT, exhibits an antiangiogenic effect as a serpin and an angiogenic effect as the precursor of Ang II.…”
Section: Discussionmentioning
confidence: 96%
“…This is controversial because quinapril, an ACE inhibitor, increased rather than decreased vascular density in a model of acute limb ischemia in the rabbit. 27 The proangiogenic activity of Ang II was first demonstrated on the chicken CAM by Le Noble et al 28 and later in a sponge model by Machado et al 29 This angiogenic effect of the renin system on microvessels has been documented in a model of electrical stimulation-induced angiogenesis. 30 It may seem paradoxical that the same molecule, AGT, exhibits an antiangiogenic effect as a serpin and an angiogenic effect as the precursor of Ang II.…”
Section: Discussionmentioning
confidence: 96%
“…Le Noble and colleagues 47 reported that Ang II may not act by influencing endothelial cell proliferation and migration like most other angiogenic factors but that its primary target is the vascular smooth muscle. Ang II may act as a mitogen for vascular smooth muscle and enhance their anchoring in the vessel wall.…”
Section: Angiogenesismentioning
confidence: 99%
“…[13][14][15] Ang II-AT1R signaling also stimulates the expression of HIF-1a and VEGF, 16,17 signals that cause neovascularization and are required for solid tumor growth. 18,19 Ang II stimulates infiltration and activation of macrophages. 20,21 In addition, AT1R signaling is shown to be associated with cancer progressions and poor prognosis in various organ type cancers.…”
Section: Introductionmentioning
confidence: 99%